2023
DOI: 10.1027/1015-5759/a000718
|View full text |Cite
|
Sign up to set email alerts
|

A Trait-Based Network Perspective on the Validation of the French Short Boredom Proneness Scale

Abstract: Abstract. The Short Boredom Proneness Scale (SBPS) has recently been developed. Using a standard confirmatory factor analysis, we report on the structural validation of the French SBPS, which provided support for the original construct. A network analysis ( n = 490) revealed the structure of the relationships between the SBPS and the two facets of Curiosity and Exploration Inventory-II (CEI-II). The analysis revealed positive connections between the boredom and curiosity items, whereas the connections between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Danckert et al (see e.g., Danckert, Mugon, et al, 2018;Mugon et al, 2018) propose that boredom-prone individuals might fail to adaptively respond to the signal of boredom, which is a trigger to action, to stop the experience of boredom and find novel opportunities to increase reward. This proposition is further supported by the results of a recent study (Martarelli, Baillifard, et al, 2022), where it was shown that while boredom-prone individuals are motivated to engage in other activities, they fail in doing so. There is a large amount of empirical work on behaviors associated with boredom proneness, paired with rather underdeveloped theorizing on the concept, which has prompted researchers to call for more careful definitions of the boredom proneness construct (Mercer-Lynn et al, 2014; and further investigation into the existence of trait boredom, as well as determining whether the existing questionnaires fully capture the construct (Gana et al, 2019).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Danckert et al (see e.g., Danckert, Mugon, et al, 2018;Mugon et al, 2018) propose that boredom-prone individuals might fail to adaptively respond to the signal of boredom, which is a trigger to action, to stop the experience of boredom and find novel opportunities to increase reward. This proposition is further supported by the results of a recent study (Martarelli, Baillifard, et al, 2022), where it was shown that while boredom-prone individuals are motivated to engage in other activities, they fail in doing so. There is a large amount of empirical work on behaviors associated with boredom proneness, paired with rather underdeveloped theorizing on the concept, which has prompted researchers to call for more careful definitions of the boredom proneness construct (Mercer-Lynn et al, 2014; and further investigation into the existence of trait boredom, as well as determining whether the existing questionnaires fully capture the construct (Gana et al, 2019).…”
supporting
confidence: 64%
“…By rewording reverse-coded items of the BPS and excluding items with poor discriminatory value, they found a one-factorial measure of eight consistently worded items. This scale showed very good internal consistency on its own (e.g., .93 in and also in its translated versions (e.g., .86 in Martarelli, Baillifard et al, 2022). Van Tilburg et al (2019) were concerned by the fact that the SBPS includes items that not directly tag boredom (e.g., "I find it hard to entertain myself") they thus created the Harthouse Boredom Proclivity Scale (HBP; item examples "How prone are you to feeling bored?"…”
mentioning
confidence: 95%
“…Boredom proneness was measured using the French and German versions of the Short Boredom Proneness Scale (SBPS; Martarelli et al, 2022;Struk et al, 2017). This scale measures an individual's general propensity to experience boredom (e.g., "I don't feel motivated by most things that I do"; see Appendix A for all items).…”
Section: Methodsmentioning
confidence: 99%
“…Second, perceiving every available action as boring should compromise behavior aiming at exploitation and exploration alike (Danckert, 2019), a prediction that is probably captured best by the characterization of boredom proneness as a "failure to launch" (Mugon et al, 2018). Indeed, people high in boredom proneness find it difficult to engage in new goals when their current goals become futile , and demonstrate weaker preferences for exploration even though they can be more curious than others (Martarelli et al, 2022). Importantly, both of these characteristics of boredom proneness-the inclination to engage in behaviors indicative of poor self-control and the failure to engage in both exploration and exploitation-are not characteristic of transient boredom discussed so far, which decreases the EVC selectively and not holistically.…”
Section: Advancing Boredom Research: An Evc Perspective On Trait Boredommentioning
confidence: 99%